ANALISIS STABILITAS MODEL VECTOR AUTOREGRESSION (VAR) PADA DATA SUKU BUNGA BI DAN INFLASI - Rakhmawati, Desty (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to analyze the stability of the Vector Autoregression (VAR) model using data on inflation and Bank Indonesia (BI) interest rates. The VAR model is a widely used econometric method for analyzing dynamic relationships between macroeconomic variables. In this research, monthly data on inflation and BI interest rates from August 2018 to August 2024 were utilized. The stability of the model was tested after performing a unit root test to assess data stationarity, followed by a stability test on the VAR model. The stability analysis of the VAR model is important to ensure that the resulting model can provide accurate predictions and is not divergent. If the model is not divergent, the predicted values remain controlled or bounded, indicating that the model is suitable for long-term use. The results show that in the unit root test, inflation data became stationary at the 2nd difference, while the BI interest rate data became stationary at the 1st difference. The stationary data were then used to build the VAR model, which was subsequently tested for stability. The stability test results, as seen from the AR Roots Table or AR Roots Graph, indicate that the VAR model is stable. Thus, the VAR model developed using these two variables satisfies the stability criteria, indicating that it can serve as a dependable tool for forecasting the dynamics between inflation and BI interest rates moving forward.